Development and validation of a new brief measure of self-efficacy in academic mastery - Yupanqui-Lorenzo, Daniel E. (2025)
Introduction: Academic self-efficacy drives achievement and student well-being; however, brief, psychometrically rigorous measures tailored to complex university courses remain scarce. Existing long‑form scales, although thorough, are often impractical for time-constrained research and classroom diagnostics. Objective: to develop and validate the five‑item Self‑Efficacy Scale in Academic Mastery (SSAM). Method: Items rooted in the Social Learning Theory were reviewed by experts (n=6). Psychometric testing used two university samples (N₁ = 180, N₂ = 742) plus the PHQ‑4. Results: Exploratory and confirmatory factor analyses supported a unidimensional structure with high reliability (α=.91; ω=.92) and good fit (CFI/TLI>.90; RMSEA/SRMR<.08). The scale showed configural, metric, and scalar invariance across the sex and academic status groups. Graded Response Model parameters indicated strong item discrimination, and structural equation modeling confirmed that higher SSAM scores predicted lower anxiety and depression. Discussion: The SSAM offers a concise, psychometric measure to assess course‑level mastery beliefs, enabling rapid screening and targeted interventions to enhance academic performance and mental health in higher education.